1995
DOI: 10.1016/0735-1097(94)00367-y
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of in-hospital and 6-month outcome after acute myocardial infarction in the reperfusion era: The primary angioplasty in myocardial infarction (PAMI) trial

Abstract: In the reperfusion era, the two most powerful determinants of freedom from death, reinfarction and recurrent ischemia after myocardial infarction are young age and treatment by primary angioplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
114
3
5

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 261 publications
(127 citation statements)
references
References 49 publications
5
114
3
5
Order By: Relevance
“…We found that patients with RI were more often elderly and female, presented later, and were more likely to have a reduced left ventricular ejection fraction, all features that have been associated with increased mortality after primary PCI for AMI. 14,18,19 Patients with RI presented with more diffuse atherosclerosis, as evidenced by more frequent peripheral vascular and cerebrovascular disease and triple-vessel coronary artery disease. Patients with RI were also less likely to be discharged on ␤-blockers, which may have contributed to reduced survival.…”
Section: Discussionmentioning
confidence: 99%
“…We found that patients with RI were more often elderly and female, presented later, and were more likely to have a reduced left ventricular ejection fraction, all features that have been associated with increased mortality after primary PCI for AMI. 14,18,19 Patients with RI presented with more diffuse atherosclerosis, as evidenced by more frequent peripheral vascular and cerebrovascular disease and triple-vessel coronary artery disease. Patients with RI were also less likely to be discharged on ␤-blockers, which may have contributed to reduced survival.…”
Section: Discussionmentioning
confidence: 99%
“…26 The Global Use of Strategies to Open Occluded Coronary Arteries in Acute Coronary Syndromes (GUSTO IIb) trial demonstrated lower 30-day mortality with PCI as compared with fibrinolysis in patients age ≥70 years. 21 Multiple small randomized trials have shown that PCI offers a mortality benefit over thrombolysis in the elderly and in high risk patients with STEMI.…”
Section: Percutaneous Coronary Interventionmentioning
confidence: 99%
“…1,2 Significant improvement in mortality and morbidity may be achieved even when reperfusion occurs up to 6 to 12 hours after acute myocardial infarction (MI). 3 However, protracted ischemia may produce an admixture of necrotic and viable myocardium. Although stunned viable myocardium differs structurally and metabolically from irreversibly injured myocardium, both may display similarly depressed mechanical function at rest early after MI.…”
mentioning
confidence: 99%